A Retailer's Decision to Join a Promotional Event of an E-commerce Platform. Issue 2 (2nd April 2020) - Khouja, Moutaz; Liu, Xin
ABSTRACT: Promotional events on e-commerce platforms (e.g., November 11 in China and Cyber Monday in the United States) have become very popular. Retailers joining these promotions sell their products on the e-commerce platform at a discount. We analyze a retailer's decision to join the e-promotion of the platform versus offering a discount on its own. Given the platform's discount factor and fees, we determine the retailer's optimal prices and the quantity to commit to the e-promotion. Our findings indicate that if the platform can help the retailer make more consumers aware of the discount, then the retailer should join the e-promotion and set the prices such that no sales to strategic consumers take place for some time interval before the e-promotion. Under incomplete information where the retailer can create a rationing risk, it may be optimal to join the e-promotion even if the platform makes fewer consumers aware of the promotion and the platform charges considerable fees. Furthermore, advance selling is found not to increase profit under complete information but to increase profit under incomplete information. Surprisingly, incomplete information on the part of consumers benefits them by lowering the average price of the product and increasing the quantity sold.